NetBeans™ IDE Field Guide: Developing Desktop, Web, Enterprise, and Mobile Applications, Second Edition - Keegan, Patrick; Champenois, Ludovic; Crawley, Gregory; Hunt, Charlie; Webster, Christopher; Jullion-Ceccarelli, John; Prazak, Jiri; Ryzl, Martin; Sporar, Gregg; Wielenga, Geertjan (Pearson, 2006)
The Only Complete Guide and Reference for NetBeans™ IDE 5.0 The award-winning NetBeans™ IDE eases all aspects of Java application development, incorporating a wide range of powerful features into one well-designed package. NetBeans IDE is consistently first in supporting the latest Java technologies for developing desktop, web, enterprise, and mobile applications. NetBeans™ IDE Field Guide provides an introduction to the IDE and an extensive range of topics to help you with both everyday and advanced programming tasks, including Taking advantage of the Ant-based project system to create easily deployable projects Developing web applications with the built-in Apache Tomcat web server Constructing, assembling, and verifying large-scale Java EE applications Managing the Sun Java System Application Server through NetBeans IDE Developing mobile applications with the NetBeans Mobility Pack In this expanded second edition, you can also learn how to Build powerful and attractive desktop applications with the Matisse GUI Builder Profile your applications for performance issues Develop modules for NetBeans IDE and rich-client applications based on the NetBeans Platform Chat and share code with other developers using the NetBeans Collaboration Modules.